Effect of Brain-Based Learning Method to Attitudes of Students in Geography Lessons - (:unkn) unknown (MARMARA UNIV, 2015)
The main purpose of this research is to determine how attitudes of students effected by brain based learning method in geography lessons. The pre- and post-test was carried out by using attitude scale on experimental and control groups. Brain based learning methods were implemented on experimental group while traditional teaching methods were used on control group. The research was conducted with 10th grade high school students in Besiktas District of Istanbul. Geography lesson attitude scale used in this research. After data collection, the data entered to SPSS 17 software program. The data analyzed by using Kolmogrov-Smirnov normality test, independent group t test, and paired group t test. Additionally, interviews and diary techniques used as a qualitative research method. According to the study, it is concluded that there are significant differences between experimental and control group in terms of attitude scores. While the brain based learning method changed the attitudes of students positively, the traditional teaching method did not change the attitude of students in geography lessons.
Keywords: Brain based learning; Geography Education; attitude